The Silver Arrow - Grossman, Lev (Little, Brown and Company, 2020)
Kate's humdrum life is transformed when her eccentric Uncle Herbert brings her a colossal locomotive train, the Silver Arrow, as her eleventh birthday gift, leading her and her younger brother on a mysterious quest.